Effects of acute and 2‐week administration of oral salbutamol on exercise performance and muscle strength in athletes. Issue 1 (31st July 2014) - Hostrup, M.; Kalsen, A.; Auchenberg, M.; Bangsbo, J.; Backer, V.
Abstract : Our objective was to investigate effects of acute and 2‐week administration of oral salbutamol on repeated sprint ability, exercise performance, and muscle strength in elite endurance athletes. Twenty male elite athletes [VO2max : 69.4 ± 1.8 (Mean ± SE) mL/min/kg], aged 25.9 ± 1.4 years, were included in a randomized, double‐blinded and placebo‐controlled parallel study. At baseline, after acute administration, and again after 2‐week administration of the study drugs (8 mg salbutamol or placebo), subjects' maximal voluntary contraction (MVC) of m. quadriceps and isometric endurance of m. deltoideus were measured, followed by three repeated Wingate tests. Exercise performance at 110% of VO2max was determined on a bike ergometer. Acute administration of salbutamol increased peak power during first Wingate test by 4.1 ± 1.7% ( P < 0.05). Two‐week administration of salbutamol increased ( P < 0.05) peak power during first and second Wingate test by 6.4 ± 2.0 and 4.2 ± 1.0%. Neither acute nor 2‐week administration of salbutamol had any effect on MVC, exercise performance at 110% of VO2max or on isometric endurance. No differences were observed in the placebo group. In conclusion, salbutamol benefits athletes' sprint ability. Thus, the present study supports the restriction of oral salbutamol in competitive sports.